MIL-101(Cr)-NH2/reduced graphene oxide composite carrier enhanced thermal conductivity and stability of shape-stabilized phase change materials for thermal energy management. (1st August 2022) - Zhou, Jianduo; Fang, Min; Yang, Kai; Lu, Kangqiang; Fei, Hua; Mu, Ping; He, Ruiqiang
Abstract: In order to address the leakage issue and enhance the thermal conductivity of phase change material (PCM), a composite carrier for shape-stabilized phase change material is developed for thermal energy management of battery. Metal organic framework (MOF): MIL-101-NH2, reduced graphene oxide (RGO), and paraffin wax (PW) were combined into a shape-stabilized CPCM to strengthen the heat transfer. MOF/RGO composite carrier was the heat transfer intensifier and the shape-stabilized container for PW. Here, the structural and thermal properties of CPCMs were evaluated by BET, SEM, XRD, FTIR, XPS, DSC, TGA and Hot Disk. The results show that MIL-101(Cr)-NH2 /RGO/PW CPCMs were successfully prepared without any chemical reaction and the CPCM with mass fraction of PW of 60% has the best thermophysical properties. The melting enthalpy of the MOF(35%)/RGO(5%)/PW(60%) CPCM after 500 thermal cycles was calculated to be 80.55 J/g, which is close to its theoretical value. The thermal conductivity of the MOF(35%)/RGO(5%)/PW(60%) CPCM is increased by 472%, which is far higher than that of pure PW. Graphical abstract: A novel shape-stabilized composite carrier is proposed to address leakage issue and low thermal conductivity of PCM for battery thermal energy management. Unlabelled Image Highlights: A novel shape-stabilized PCM for thermal energy management of battery is proposed. The MOF/RGO composite carrier has a good encapsulation efficiency. The MOF/RGO composite carrier can obviously enhance thermal conductivity. The PCM adsorb by MOF/RGO composite carrier has heat endurance.